2016
DOI: 10.1111/epi.13572
|View full text |Cite
|
Sign up to set email alerts
|

Ripples on spikes show increased phase‐amplitude coupling in mesial temporal lobe epilepsy seizure‐onset zones

Abstract: Objective Ripples (80–150 Hz) recorded from clinical macroelectrodes have been shown to be an accurate biomarker of epileptogenic brain tissue. We investigated coupling between epileptiform spike phase and ripple amplitude to better understand the mechanisms that generate this type of pathological ripple (pRipple) event. Methods We quantified phase amplitude coupling (PAC) between epileptiform EEG spike phase and ripple amplitude recorded from intracranial depth macroelectrodes during episodes of sleep in 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 43 publications
8
67
0
Order By: Relevance
“…A 2–5-fold increase in the rate of ripples in the seizure onset zone, relative to the NSOZ, was evident in patients with mesial temporal lobe epilepsy, mesial temporal lobe epilepsy plus (Barba et al, 2007, 2016), and neocortical epilepsy. The accuracy of ripple rates for classifying the SOZ is consistent with previously published studies (Jacobs et al, 2008, 2009; Worrell et al, 2008; Wang et al, 2013; Weiss et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A 2–5-fold increase in the rate of ripples in the seizure onset zone, relative to the NSOZ, was evident in patients with mesial temporal lobe epilepsy, mesial temporal lobe epilepsy plus (Barba et al, 2007, 2016), and neocortical epilepsy. The accuracy of ripple rates for classifying the SOZ is consistent with previously published studies (Jacobs et al, 2008, 2009; Worrell et al, 2008; Wang et al, 2013; Weiss et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
“…Prior investigations have also demonstrated that ripples on spike rates are better than ripple on oscillation rates for delineating the seizure onset zone (Wang et al, 2013; Weiss et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…One-second trials of ripples occurring on inter-ictal discharges were identified using a previously described algorithm (Weiss et al, 2016b; Shimamoto et al, 2018). In brief, (1) INFOMAX independent component analysis (Bell and Sejnowski, 1997) was applied to referential recordings to reduce muscle contamination, and demarcate artefactual ripple events produced by muscle contamination (2) ripples were detected using a Hilbert detector applied to the band-pass filtered and ICA processed signal, (3) for each ripple detected a one-second trial was generated with a ripple centered at 0.5 s, (4) To distinguish ripples that occur during epileptiform spikes from all other ripples, we utilized a validated method (Shimamoto et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In both manual and automated HFO detection, it is common practice to first apply a high pass filter to the continuous intracranial EEG (iEEG) or local field potential (LFP) recordings (Weiss et al, 2016a, 2016b). After high-pass filtering, HFOs can be observed visually or detected automatically as an increase in the signal amplitude above a threshold of 3–5 standard deviations of the mean for at least three oscillatory cycles (Csicsvari et al, 1999; Staba et al, 2002; Weiss et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation